Design thinking in the customer journey in a sports center - Barbosa, Priscila Pasti (2023)
Design thinking and the customer journey play a fundamental role in improving service in sports centers. By adopting user-centered approaches, sports facilities can better understand patrons' needs, wants and experiences. Design thinking allows managers of these centers to identify opportunities for innovation, develop creative solutions to improve facilities and services, and test these ideas in collaboration with users. By mapping the customer journey, from the first interaction to the post-experience, it is possible to identify critical touchpoints and areas for possible improvements. This not only creates more attractive and functional sporting environments, but also helps build stronger customer relationships, promoting loyalty and satisfaction, which are critical to the long-term success of these establishments. In this article, the authors developed an understanding of the experience that customers of a sports complex are obtaining in relation to the service offered. To achieve this objective, they examined existing definitions and conceptualizations through a brief systematic review of the literature. They then used the design thinking approach and its customer journey tool, in which personas were determined for the sports complex. Next, they carried out the visual development of the customer journey using the value proposition canvas tool, thus obtaining a description of the personas, their journey, what is expected and what they receive from the service, the sentiment curve, as well as their opportunities and pain. Finally, the authors arrived at 3 personas, totaling 25 points of contact, which made it possible to develop actions with the aim of improving the customer experience in the case in question.